Multifunctional Green Wall Systems for Greywater Treatment and Hygrothermal Regulation in Egypt - Abdelsalam, Laila Ossama Mohamed Elhusseiny (AUC Knowledge Fountain, 2026)
Increasing environmental concerns regarding climate change and the intensifying challenge of water scarcity in Egypt necessitate the development of innovative, sustainable, and resource-efficient strategies for wastewater reuse. In the built environment, greywater constitutes a significant, relatively low-contaminant wastewater stream that, if treated to comply with Egyptian Codes and relevant international standards, can be safely reused for non-potable applications such as irrigation, landscaping, and building services. This research investigates the efficacy of an integrated green wall panel system, installed on building façades, for decentralized greywater treatment under Egypt’s climatic and environmental conditions, while simultaneously enhancing hygrothermal performance to reduce building energy demand. The proposed green wall system was developed as a multilayer treatment assembly incorporating sequential filtration stages and vegetation, designed for concurrent greywater treatment and environmental performance enhancement. Experimental optimization of the primary filtration stage (Phases I–II) identified a medium composed of 50% sand and 50% activated carbon as the most effective configuration, achieving the highest contaminant removal efficiency and outperforming other tested ratios and filtration media in reducing turbidity and pollutant loads. Phase III results demonstrated that Canna indica, characterized by its extensive fibrous root system, consistently outperformed Ruscus aculeatus across all seven water quality parameters, achieving superior removal efficiencies. The temporal analysis revealed significant performance improvements over successive experimental runs, confirming the system's capacity for optimization and long-term viability. The optimized Canna indica green wall system achieved compliance with major regional and international reuse standards. Annual scaling analysis confirmed a treatment potential on a multi-story building, highlighting its feasibility as a sustainable decentralized wastewater management solution. In Phase IV, two plant species; Canna indica and Ruscus aculeatus, were comparatively evaluated for their phytoremediation capacity and hygrothermal performance. Canna indica proved more effective in lowering internal air temperatures within adjacent test chambers and enhancing indoor microclimatic conditions through improved relative humidity. These hygrothermal improvements were further validated through Heat Index calculations, which quantitatively demonstrated Canna indica's superior performance in 1 reducing indoor thermal stress, decreasing cooling energy demand, and generating enhanced cost savings. Taken together with its higher greywater purification efficiency, Phase IV demonstrated that the Canna indica green wall offers the strongest potential to serve as a dual-function system, integrating decentralized wastewater treatment with passive thermal regulation to enhance both environmental performance and energy savings in sustainable building design. Overall, the findings demonstrate that optimized green wall panel configurations can consistently produce high-quality treated greywater meeting both Egyptian and international reuse standards while delivering co-benefits such as façade shading, thermal buffering, and microclimate enhancement. The study concludes that integrating greywater treatment into green wall systems represents a viable dual-function strategy for water reuse and energy efficiency in water-stressed and hot-climate regions. However, it also identifies the need for further research into long-term performance, standardized maintenance protocols, and design refinements to enable large-scale implementation.